"I Desire Sanctity": Sanctity and Separateness among Jewish Religious Zionists in Israel/Palestine. (September 2015) - Stern, Nehemia Akiva
Abstract This article expands on anthropological understandings of affect and emotion to include certain theological and religious concepts that structure and give meaning to the daily lives of religious nationalists in areas of ethnic and political conflict. In doing so, it will ethnographically explore the relationship between theological notions of sanctity and the way those notions manifest themselves in the context of contemporary Jewish religious Zionism in both Israel and the Occupied West Bank. I will argue that analyzing mystical conceptions of sanctity as a distinct affect opens new areas of human experience, which anthropologists may use to better grapple with the dilemmas posed by nationalism and religious extremism in an increasingly politically fraught world.